The agreement between emergency department and intensive care unit depth of sedation assessment - Lokhandwala, Sharukh (My University, 2019)
RATIONALE: During mechanical ventilation, assessment and treatment of pain and agitation are important to ease patient discomfort, allow for ventilator synchrony, and decrease work of breathing. Despite this, it is uncommon for patients intubated in the emergency department(ED) to have level of sedation documented using a standardized scale. Studies focused on early depth of sedation frequently use first intensive care unit (ICU) sedation assessment as a proxy for ED depth of sedation; however, little evidence supports this practice. We sought to demonstrate the level of agreement between Richmond Agitation and Sedation Scale (RASS) measurements documented in the ED and the initial ICU RASS. METHODS We performed a secondary analysis of LOTUS-FRUIT, a prospective cohort study of patients with acute respiratory failure requiring intubation at PETAL network institutions. Patients who were intubated in the prehospital or emergency setting and had a documented ED RASS were included. The period of analysis was from time of intubation to ICU admission. Weighted Cohen’s Kappa was used to compare agreement between ED and initial ICU RASS. McNemar’s test was used to compare documentation of deep sedation (RASS -3 to -5) in the ED and ICU. RESULTS: Of the 784 patients who were intubated in the pre-hospital setting or ED, 180 had both an ED and initial ICU RASS documented. The most common indications for mechanical ventilation were respiratory failure (47.8%) and altered mental status (42.2%). The median time from intubation to ICU arrival was 4 hours (IQR 2.2-5.8). Most patients were admitted to a medical ICU (52.8%) followed by mixed (19.4%), surgical (14.4%), cardiac (8.9%) and neurological (4.4%) ICUs. Using a quadratic weighted kappa, ED and ICU RASS demonstrated substantial agreement (kappa=0.64). There was no statistically significant difference in the proportion with deep sedation between ED and ICU (p=0.51). CONCLUSIONS: ED and ICU RASS measurements demonstrate substantial agreement. Although RASS assessments occurred uncommonly in the ED overall, when RASS in the ED was documented, patients were equally likely to be categorized as deeply sedated in the ED and on admission to the ICU. In settings where depth of sedation is not routinely measured in the ED, first ICU depth of sedation may serve as an appropriate proxy.
Thesis (Master's)--University of Washington, 2019
Keywords: critical care; mechanical ventilation; sedation; Medicine; Epidemiology